THE IMPORTANCE AND PERFORMANCE ANALYSIS OF SERVICE QUALITY AND PRICE ON GO-RIDE FEATURE IN MANADO - Kantale, Andreas .; Lapian, S. L. H. V. Joyce; Pandowo, Merinda . (Universitas Sam Ratulangi, 2017)
Abstract: Transportation has become one of the most important services for supporting people’s daily activities. The presence of GO-JEK in Manado become a phenomena since this kind of online-based application as transportation service provider had used by mostly people especially for Go-Ride Feature. This research aims to analyze the service quality and price of Go-Ride Feature on GO-JEK application in Manado. Type of this research is descriptive with quantitative approach and IPA used as the measurement tool. The sample size of this research is 100 respondents who already experience the Go-Ride feature on GO-JEK application in Manado. Convenience sampling was used by collecting data through online questionnaire. The result for service quality shows, Go-Ride’s driver skill is very important to the customers and PT.GOJEK delivered good performance to the customers, this attribute located in Quadrant 2. The completeness attributes of Go-Ride drivers is the lowest average of importance and performance for service quality. The result for price shows that, affordability price is the highest level of importance and performance. Meanwhile the attributes such are: Go-Ride feature’s price comparable with the facilities and price is cheaper than other public transportation, those attributes are located in Quadrant 3 with the low average.Keywords: importance and performance analysis, service quality, price, go-ride, go-jek.